ANALISIS PENGARUH DEBT TO ASSET RATIO, RETURN ON ASSET, NET PROFIT MARGIN, TERHADAP HARGA SAHAM DI SEKTOR PERDAGANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - ZARIYAH ZARIYAH (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
ABSTRACTThis study aims to analyze Return On Assets, Debt To Asset Ratio and Net Profit Margin at the price of shares listed on the Indonesian Stock Exchange (IDX) for the period 2011-2013. Share prices are formed from the process of supply and demand that occurs in exchange. In addition, the stock price factor can be seen from the calculation of the company's financial ratios contained in the financial statements published on the Indonesia Stock Exchange (IDX). This research was conducted by purposive sampling with a sample of 104 companies. Data analysis used is multiple linear regression analysis. The results show that the net profit margin has no effect on stock prices, while the ratio of return on assets affects the stock price. From the test variables simultaneously the debt to asset ratio and net profit margin simultaneously have a significant effect on stock price prices on stock prices. The results of this study indicate that the net profit margin has no effect on stock price. And the ratio of debt to assets, return on assets and net profit margin has a significant effect on stock price prices.to explain these three variables.